Preparation method and application of electrode material binder with high ionic conductivity and high voltage resistance
By introducing polyethylene ethylene-lithium salt mixture and high-voltage additives in the adhesive to prepare high-ion conductivity and high-voltage electrode material adhesives, traditional adhesives are solved The problem of wearing has achieved higher reliability and electrochemical properties.
Patent Information
- Application Number
- CN202411264151.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-09-10
AI Technical Summary
Traditional binders are prone to breakdown and failure in high voltage environments, limiting the reliability and service life of the device, especially in areas such as electric vehicles, grid energy storage and portable electronic devices.
By introducing polyethylene-lithium salt mixed fluids and high-voltage additives, such as spinthophenyl boric acid PFBBA or tetraraphic boric acid, high ion conductivity and electrode material adhesives with high voltage resistance are prepared.
The long -term stable cycle of adhesive under high -electric field conditions is achieved, the service life of electronic devices and energy storage systems is significantly extended, the reliability and durability of the equipment are improved, and the electrochemical performance and energy density is improved.
Smart Images

Figure BDA0005036662430000091 
Figure HDA0005036662440000011 
Figure HDA0005036662440000012
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a preparation method and application of a binder with high ionic conductivity and high voltage resistance. Background Art
[0002] In modern electronic devices and energy storage systems, adhesives are key components that play a vital role in the performance and stability of the equipment. Although traditional adhesives can meet basic needs under certain conditions, they often perform poorly in high voltage environments and are prone to breakdown and failure, thus limiting the reliability and service life of the device. This problem is particularly evident in areas such as electric vehicles, grid energy storage, and portable electronic devices, as these applications have extremely high requirements for high voltage stability and long-term performance.
[0003] In order to address these limitations of traditional adhesives, researchers are actively exploring and developing new adhesives with high ionic conductivity and high voltage resistance. This type of adhesive can not only effectively transport electrons and ions, but also maintain stability under high electric field conditions, thereby significantly improving the performance and reliability of the device. High ionic conductivity enables the adhesive to effectively promote the transmission of electrons and ions, helping to improve the efficiency and response speed of the device; while the high voltage resistance ensures that no breakdown or damage occurs under high voltage stress, extending the life and stability of the device.
[0004] The development of new binders not only depends on the electrical and chemical properties of the material itself, but also requires precise control of its composition and structure. Through rational design and process optimization, researchers can achieve customized requirements for binders in different application scenarios, thereby promoting technological progress and innovation in electronic devices and energy storage systems. For example, in lithium-ion batteries, optimized binders can improve the structural stability and electrochemical properties of electrode materials, thereby improving the cycle life and energy density of the battery.
[0005] Overall, the development and application of binders with high ionic conductivity and high voltage resistance is not only a technical challenge, but also a key factor in promoting the development of electronic devices and energy storage. Future research will continue to explore new materials, optimize processes and application innovations to meet the growing demand for high-performance and high-reliability devices. Summary of the invention
[0006] In view of the deficiencies of the prior art, the present invention discloses a method for preparing a binder with high ionic conductivity and high voltage resistance. The prepared binder has both high ionic conductivity and excellent high voltage resistance.
[0007] The technical solution of the present invention is:
[0008] A method for preparing a binder with high ionic conductivity and high voltage resistance comprises the following steps:
[0009] Step 1: Prepare polyethylene oxide-lithium salt mixture
[0010] Dissolve polyethylene oxide in deionized water and stir at room temperature for 24 hours to prepare a polyethylene oxide solution, and add lithium salt in a polyethylene oxide to lithium salt mass ratio of 12:1 to obtain a polyethylene oxide-lithium salt mixed solution;
[0011] Step 2: Preparation of electrode material binder
[0012] The sodium carboxymethyl cellulose aqueous solution and the polyethylene oxide-lithium salt mixed solution were mixed in a mass ratio of 10:1, and stirred at room temperature for 12 hours to obtain an electrode material binder;
[0013] Step 3: Preparation of high ionic conductivity and high voltage resistant electrode material binder
[0014] The electrode material binder and the high voltage resistant additive are mixed in a mass ratio of 10:(0-1.5), wherein the high voltage resistant additive is one or two of pentafluorophenylboric acid PFBBA and tetramethyl borate (TMB); and an electrode material binder with high ionic conductivity and high voltage resistance is obtained.
[0015] Furthermore, the electrode material binder and the high voltage resistant additive are in a mass ratio of 10:(0.5-1.5).
[0016] Furthermore, the lithium salt is at least one of lithium hexafluorophosphate LiFP6, lithium tetrafluoroborate LiBF4, lithium bis(oxalatoborate) LiBOB, lithium bis(trifluoromethylsulfonyl)imide LiTFSI, lithium bis(fluorooxalatoborate) LiODFB, and lithium bis(fluorosulfonyl)imide LiFSI.
[0017] Furthermore, the mass concentration of the sodium carboxymethyl cellulose solution is 1.2%.
[0018] Furthermore, when preparing the polyethylene oxide aqueous solution, the stirring time is 24 hours.
[0019] An application of the above-mentioned binder with high ionic conductivity and high voltage resistance in the preparation of an electrode positive electrode.
[0020] Furthermore, the electrode material binder, active material and conductive agent are mixed to prepare pulp, and the high-voltage resistant additive is added during the pulping process. The high-voltage resistant additive is one or two of pentafluorophenylboric acid PFBBA and tetramethyl borate (TMB), and the amount of the high-voltage resistant additive added accounts for 0.5-1.5% of the total mass of the electrode material binder, active material and conductive agent. After stirring evenly, the mixture is coated on an aluminum foil current collector to obtain a positive electrode sheet.
[0021] Furthermore, the mass ratio of the electrode material binder to the active material and the conductive agent is 10:85:5.
[0022] Furthermore, the conductive agent is selected from one or two of Super P and acetylene black; the active material is selected from one of ternary materials (NCM811, NCM622, NCM532), lithium cobalt oxide, lithium nickel oxide, and lithium-rich manganese materials; and the conductive agent is selected from one or more of Super P, acetylene black, carbon nanotubes or graphene.
[0023] Furthermore, the lithium-rich manganese material is 0.5Li2MnO3·0.5LiNi 0.33 Co 0.33 Mn 0.33 O2.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] (1) The present invention introduces polymer chains that can promote lithium ion migration, greatly improving the ionic conductivity of the binder. In addition, by introducing high-voltage resistant additives, long-term stable cycling under high voltage is achieved. Experimental verification shows that this composite modification method can further improve the electrochemical performance of the positive electrode material.
[0026] (2) High ionic conductivity and high voltage resistance The electrode material binder has excellent high voltage resistance and can remain stable under high electric field conditions, and is not prone to breakdown or damage. This stability significantly extends the service life of electronic devices and energy storage systems (such as lithium-ion batteries), especially for long-term or high-voltage operation scenarios, improving the reliability and durability of the equipment.
[0027] (3) High ionic conductivity and high voltage resistance The electrode material binder has high ionic conductivity, can efficiently transmit ions, and optimize the contact and electron transmission between the electrode material and the electrolyte. It can effectively transmit ions. For example, in lithium-ion batteries, it can promote good contact and electron transmission between the electrode material and the electrolyte, thereby improving the energy density and charge and discharge efficiency of the battery. New binders with high ionic conductivity and high voltage resistance can not only significantly improve the performance and reliability of the equipment, but also provide stronger power support and faster response speed for the equipment.
[0028] (4) The modified lithium-rich manganese-based positive electrode material prepared by the high ionic conductivity and high voltage resistant electrode material binder of the present invention has a discharge specific capacity of up to 295.51 mAh / g, and the capacity retention rate can still reach 102.14% after 400 cycles, which has both high capacity and high cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The first charge and discharge curve at 30°C and 0.1C rate after assembling a battery based on a modified binder lithium-rich manganese-based positive electrode material according to the present invention (corresponding to Example 1);
[0030] Figure 2 The discharge specific capacity decay diagram of the battery assembled with the modified binder lithium-manganese-based positive electrode material at 30°C 1C for 400 cycles according to the present invention (corresponding to Example 1);
[0031] Figure 3 The median voltage decay diagram of the battery assembled based on the modified binder lithium-rich manganese-based positive electrode material of the present invention (corresponding to Example 1) after 400 cycles at 30°C 1C;
[0032] Figure 4 This is a graph of the lithium ion diffusion coefficient of a battery assembled based on a modified binder lithium-rich manganese-based positive electrode material according to the present invention (corresponding to Example 1);
[0033] Figure 5 The first charge and discharge curve at 30°C and 0.1C rate after assembling a battery based on a modified binder lithium-rich manganese-based positive electrode material according to the present invention (corresponding to Example 2);
[0034] Figure 6 The discharge specific capacity decay diagram of the battery assembled based on the modified binder lithium-manganese-based positive electrode material of the present invention (corresponding to Example 2) after 400 cycles at 30°C 1C;
[0035] Figure 7 The median voltage decay diagram of the battery assembled based on the modified binder lithium-rich manganese-based positive electrode material of the present invention (corresponding to Example 2) after 400 cycles at 30°C 1C;
[0036] Figure 8 The first charge and discharge curve at 30°C and 0.1C rate after assembling a battery based on a modified binder lithium-rich manganese-based positive electrode material according to the present invention (corresponding to Example 3);
[0037] Fig. 9 The discharge specific capacity decay diagram of the battery assembled with the modified binder lithium-manganese-based positive electrode material at 30°C 1C for 400 cycles according to the present invention (corresponding to Example 3);
[0038] Fig.10 The median voltage decay diagram of the battery assembled with the modified binder lithium-rich manganese-based positive electrode material at 30°C 1C for 400 cycles according to the present invention (corresponding to Example 3);
[0039] Fig.11 The first charge and discharge curve at 30°C and 0.1C rate after assembling a battery based on a modified binder lithium-rich manganese-based positive electrode material according to the present invention (corresponding to Example 4);
[0040] Fig.12 The discharge specific capacity decay diagram of the battery assembled based on the modified binder lithium-manganese-based positive electrode material of the present invention (corresponding to Example 4) after 400 cycles at 30°C 1C;
[0041] Fig.13 This is a TEM image of the battery assembled with the modified binder lithium-manganese-based positive electrode material according to the present invention (corresponding to Example 4) after 400 cycles at 30°C 1C;
[0042] Fig.14 The median voltage decay diagram of the battery assembled based on the modified binder lithium-manganese-based positive electrode material of the present invention (corresponding to Example 4) after 400 cycles at 30°C 1C;
[0043] Fig.15 This is a graph of the lithium ion diffusion coefficient of a battery assembled based on a modified binder lithium-rich manganese-based positive electrode material according to the present invention (corresponding to Example 4);
[0044] Fig.16 The first charge and discharge curve at 30°C and 0.1C rate after assembling the battery with the product prepared in the present invention (corresponding to Example 1);
[0045] Fig.17 The discharge capacity decay diagram of the battery assembled with the product prepared in the present invention (corresponding to Example 1) after 400 cycles at 30°C 1C;
[0046] Fig.18 This is a TEM image of a battery assembled from a product prepared in the present invention (corresponding to Example 1) after 400 cycles at 30°C 1C;
[0047] Fig.19 The median voltage decay diagram of the battery assembled with the product prepared in the present invention (corresponding to Example 1) after 400 cycles at 30°C 1C;
[0048] Fig. 20 This is a graph of the lithium ion diffusion coefficient of the battery assembled from the product prepared in the present invention (corresponding to Example 1). DETAILED DESCRIPTION
[0049] The present invention is further described in detail below in conjunction with examples and comparative examples, but the embodiments of the present invention are not limited thereto.
[0050] Example 1
[0051] (1) dissolving sodium carboxymethyl cellulose in deionized water and stirring at room temperature for 24 hours to prepare a sodium carboxymethyl cellulose aqueous solution with a mass concentration of 1.2%;
[0052] (2) dissolving polyethylene oxide in deionized water and stirring at room temperature for 24 hours to prepare a polyethylene oxide aqueous solution with a mass concentration of 1.2%, and adding lithium salt LiBOB according to a mass ratio of polyethylene oxide to lithium salt of 12:1 to obtain a polyethylene oxide-lithium salt mixed solution;
[0053] (3) mixing the sodium carboxymethyl cellulose aqueous solution and the polyethylene oxide-lithium salt mixed solution in a mass ratio of 10:1, and stirring at room temperature for 12 hours to obtain an electrode material binder;
[0054] (4) The electrode material binder prepared in step (3) is mixed with the lithium-rich manganese positive electrode material 0.5Li2MnO3·0.5LiNi 0.33 Co 0.33 Mn 0.33 O2 and Super P are mixed into a slurry in a mass ratio of 10:85:5; after being stirred evenly, the slurry is coated on an aluminum foil current collector to obtain a positive electrode plate, which is recorded as CPL.
[0055] The above-mentioned positive electrode sheet was used, and the metal Li sheet was used as the reference electrode and the counter electrode. The diaphragm was Celgard 2400, and the electrolyte was Xinzhoubang 3045I. The assembly was carried out in a glove box filled with argon gas with oxygen and water content less than 0.01ppm. Its electrochemical performance was tested for charge and discharge using a 2025 button cell on the Xinwei test system, and the test voltage window was 2.0~4.8V. The test temperature was 27±1℃, and the first three cycles were activated at a rate of 0.1C (1C=200mAh / g), and the 1C rate cycle was used from the 4th cycle. The performance test results are listed in Table 1.
[0056] Example 2
[0057] (1) dissolving sodium carboxymethyl cellulose in deionized water and stirring at room temperature for 24 hours to prepare a sodium carboxymethyl cellulose aqueous solution with a mass concentration of 1.2%;
[0058] (2) dissolving polyethylene oxide in deionized water and stirring at room temperature for 24 hours to prepare a polyethylene oxide aqueous solution with a mass concentration of 1.2%, and adding lithium salt LiBOB according to a mass ratio of polyethylene oxide to lithium salt of 12:1 to obtain a polyethylene oxide-lithium salt mixed solution;
[0059] (3) mixing the sodium carboxymethyl cellulose aqueous solution and the polyethylene oxide-lithium salt mixed solution in a mass ratio of 10:1, and stirring at room temperature for 12 hours to obtain an electrode material binder;
[0060] (4) The electrode material binder prepared in step (3) is mixed with the lithium-rich manganese positive electrode material 0.5Li2MnO3·0.5LiNi 0.33 Co 0.33 Mn 0.33O2 and Super P are mixed into a slurry in a mass ratio of 10:85:5. Pentafluorophenylboric acid PFBBA is added during the slurry making process. The addition ratio is 0.5% of the total mass of the electrode material binder, lithium manganese-rich positive electrode material and Super P. After stirring evenly, it is coated on an aluminum foil current collector to obtain a positive electrode sheet, which is recorded as CPL-0.5%PF.
[0061] The battery assembly process is the same as in Example 1, and the performance test results are listed in Table 1.
[0062] Example 3
[0063] (1) dissolving sodium carboxymethyl cellulose in deionized water and stirring at room temperature for 24 hours to prepare a sodium carboxymethyl cellulose aqueous solution with a mass concentration of 1.2%;
[0064] (2) dissolving polyethylene oxide in deionized water and stirring at room temperature for 24 hours to prepare a polyethylene oxide aqueous solution with a mass concentration of 1.2%, and adding lithium salt LiBOB according to a mass ratio of polyethylene oxide to lithium salt of 12:1 to obtain a polyethylene oxide-lithium salt mixed solution;
[0065] (3) mixing the sodium carboxymethyl cellulose aqueous solution and the polyethylene oxide-lithium salt mixed solution in a mass ratio of 10:1, and stirring at room temperature for 12 hours to obtain an electrode material binder;
[0066] (4) The electrode material binder prepared in step (3) is mixed with the lithium-rich manganese positive electrode material 0.5Li2MnO3·0.5LiNi 0.33 Co 0.33 Mn 0.33 O2 and Super P are mixed into a slurry in a mass ratio of 10:85:5. Pentafluorophenylboric acid PFBBA is added during the slurry making process. The addition ratio is 1.0% of the total mass of the electrode material binder, the lithium manganese-rich positive electrode material and Super P. After stirring evenly, it is coated on an aluminum foil current collector to obtain a positive electrode sheet, which is recorded as CPL-1.0%PF.
[0067] The battery assembly process is the same as in Example 1, and the performance test results are listed in Table 1.
[0068] Example 4
[0069] (1) dissolving sodium carboxymethyl cellulose in deionized water and stirring at room temperature for 24 hours to prepare a sodium carboxymethyl cellulose aqueous solution with a mass concentration of 1.2%;
[0070] (2) dissolving polyethylene oxide in deionized water and stirring at room temperature for 24 hours to prepare a polyethylene oxide aqueous solution with a mass concentration of 1.2%, and adding lithium salt LiBOB according to a mass ratio of polyethylene oxide to lithium salt of 12:1 to obtain a polyethylene oxide-lithium salt mixed solution;
[0071] (3) mixing the sodium carboxymethyl cellulose aqueous solution and the polyethylene oxide-lithium salt mixed solution in a mass ratio of 10:1, and stirring at room temperature for 12 hours to obtain an electrode material binder;
[0072] (4) The electrode material binder prepared in step (3) is mixed with the lithium-rich manganese positive electrode material 0.5Li2MnO3·0.5LiNi 0.33 Co 0.33 Mn 0.33 O2 and Super P are mixed into a slurry in a mass ratio of 10:85:5. Pentafluorophenylboric acid PFBBA is added during the slurry making process. The addition ratio is 1.5% of the total mass of the electrode material binder, lithium manganese-rich positive electrode material and Super P. After stirring evenly, it is coated on an aluminum foil current collector to obtain a positive electrode sheet, which is recorded as CPL-1.5%PF.
[0073] The battery assembly process is the same as in Example 1, and the performance test results are listed in Table 1.
[0074] Example 5
[0075] (1) dissolving sodium carboxymethyl cellulose in deionized water and stirring at room temperature for 24 hours to prepare a sodium carboxymethyl cellulose aqueous solution with a mass concentration of 1.2%;
[0076] (2) dissolving polyethylene oxide in deionized water and stirring at room temperature for 24 hours to prepare a polyethylene oxide aqueous solution with a mass concentration of 1.2%, and adding lithium salt LiBOB according to a mass ratio of polyethylene oxide to lithium salt of 12:1 to obtain a polyethylene oxide-lithium salt mixed solution;
[0077] (3) mixing the sodium carboxymethyl cellulose aqueous solution and the polyethylene oxide-lithium salt mixed solution in a mass ratio of 10:1, and stirring at room temperature for 12 hours to obtain an electrode material binder;
[0078] (4) The electrode material binder prepared in step (3) is mixed with the lithium-rich manganese positive electrode material 0.5Li2MnO3·0.5LiNi 0.33 Co 0.33 Mn 0.33 O2 and Super P are mixed into a slurry in a mass ratio of 10:85:5. Tetramethyl borate TMB is added during the slurry making process, and the addition ratio is 0.5% of the total mass of the electrode material binder, the lithium manganese-rich positive electrode material, and Super P; after stirring evenly, it is coated on an aluminum foil current collector to obtain a positive electrode sheet, which is recorded as CPL-0.5% TMB.
[0079] The battery assembly process is the same as in Example 1, and the performance test results are listed in Table 1.
[0080] Example 6
[0081] (1) dissolving sodium carboxymethyl cellulose in deionized water and stirring at room temperature for 24 hours to prepare a sodium carboxymethyl cellulose aqueous solution with a mass concentration of 1.2%;
[0082] (2) dissolving polyethylene oxide in deionized water and stirring at room temperature for 24 hours to prepare a polyethylene oxide aqueous solution with a mass concentration of 1.2%, and adding lithium salt LiBOB according to a mass ratio of polyethylene oxide to lithium salt of 12:1 to obtain a polyethylene oxide-lithium salt mixed solution;
[0083] (3) mixing the sodium carboxymethyl cellulose aqueous solution and the polyethylene oxide-lithium salt mixed solution in a mass ratio of 10:1, and stirring at room temperature for 12 hours to obtain an electrode material binder;
[0084] (4) The electrode material binder prepared in step (3) is mixed with the lithium-rich manganese positive electrode material 0.5Li2MnO3·0.5LiNi 0.33 Co 0.33 Mn 0.33 O2 and Super P are mixed into a slurry in a mass ratio of 10:85:5. Tetramethyl borate TMB is added during the slurry making process, and the addition ratio is 1.0% of the total mass of the electrode material binder, the lithium manganese-rich positive electrode material, and Super P; after stirring evenly, it is coated on an aluminum foil current collector to obtain a positive electrode sheet, which is recorded as CPL-1.0% TMB.
[0085] The battery assembly process is the same as in Example 1, and the performance test results are listed in Table 1.
[0086] Example 7
[0087] (1) dissolving sodium carboxymethyl cellulose in deionized water and stirring at room temperature for 24 hours to prepare a sodium carboxymethyl cellulose aqueous solution with a mass concentration of 1.2%;
[0088] (2) dissolving polyethylene oxide in deionized water and stirring at room temperature for 24 hours to prepare a polyethylene oxide aqueous solution with a mass concentration of 1.2%, and adding lithium salt LiBOB according to a mass ratio of polyethylene oxide to lithium salt of 12:1 to obtain a polyethylene oxide-lithium salt mixed solution;
[0089] (3) mixing the sodium carboxymethyl cellulose aqueous solution and the polyethylene oxide-lithium salt mixed solution in a mass ratio of 10:1, and stirring at room temperature for 12 hours to obtain an electrode material binder;
[0090] (4) The binder prepared in step (3) is mixed with the lithium-rich manganese positive electrode material 0.5Li2MnO3·0.5LiNi 0.33 Co 0.33 Mn 0.33O2 and Super P are mixed into a slurry in a mass ratio of 10:85:5. Tetramethylborate TMB is added during the slurrying process, and the addition ratio is 1.5% of the total mass of the electrode material binder, lithium manganese-rich positive electrode material, and Super P; after stirring evenly, it is coated on an aluminum foil current collector to obtain a positive electrode sheet, which is recorded as CPL-1.5% TMB.
[0091] The battery assembly process is the same as in Example 1, and the performance test results are listed in Table 1.
[0092] Comparative Example 1
[0093] (1) dissolving sodium carboxymethyl cellulose in deionized water and stirring at room temperature for 24 hours, wherein the sodium carboxymethyl cellulose solution having a concentration of 1.2% is used as a binder;
[0094] (2) The binder sodium carboxymethyl cellulose solution prepared in step (1) is mixed with the lithium-rich manganese positive electrode material 0.5Li2MnO3·0.5LiNi 0.33 Co 0.33 Mn 0.33 O2 and Super P were mixed into slurry in a mass ratio of 10:85:5; the product was recorded as CMC, and the battery assembly process was the same as in Example 1. The performance test results are listed in Table 1.
[0095] Comparative Example 2
[0096] (1) dissolving sodium carboxymethyl cellulose in deionized water and stirring at room temperature for 24 hours to prepare a sodium carboxymethyl cellulose aqueous solution with a mass concentration of 1.2%;
[0097] (2) dissolving polyethylene oxide in deionized water and stirring at room temperature for 24 hours to prepare a polyethylene oxide aqueous solution with a mass concentration of 1.2%;
[0098] (3) mixing the sodium carboxymethyl cellulose aqueous solution and the polyethylene oxide aqueous solution, and continuing to stir at room temperature for 12 hours, wherein the mass ratio of the sodium carboxymethyl cellulose aqueous solution to the polyethylene oxide aqueous solution is 10:1 (without adding lithium salt), to obtain an electrode material binder;
[0099] (4) The electrode material binder prepared in step (3) is mixed with the lithium-rich manganese positive electrode material 0.5Li2MnO3·0.5LiNi 0.33 Co 0.33 Mn 0.33 O2 and Super P were mixed into slurry in a mass ratio of 10:85:5; the product was recorded as CP. The battery assembly process was the same as in Example 1, and the performance test results are listed in Table 1.
[0100] Comparative Example 3
[0101] (1) dissolving sodium carboxymethyl cellulose in deionized water and stirring at room temperature for 24 hours to prepare a sodium carboxymethyl cellulose aqueous solution with a mass concentration of 1.2%;
[0102] (2) dissolving polyethylene oxide in deionized water and stirring at room temperature for 24 hours to prepare a polyethylene oxide aqueous solution with a mass concentration of 1.2%, and adding lithium salt LiBOB according to a mass ratio of polyethylene oxide to lithium salt of 12:1 to obtain a polyethylene oxide-lithium salt mixed solution;
[0103] (3) mixing the sodium carboxymethyl cellulose aqueous solution and the polyethylene oxide-lithium salt mixed solution in a mass ratio of 1:1, and stirring at room temperature for 12 hours to obtain an electrode material binder;
[0104] (4) The electrode material binder prepared in step (3) is mixed with the lithium-rich manganese positive electrode material 0.5Li2MnO3·0.5LiNi 0.33 Co 0.33 Mn 0.33 O2 and Super P were mixed into a slurry in a mass ratio of 10:85:5; after being stirred evenly, the slurry was coated on an aluminum foil current collector to obtain a positive electrode sheet, which was recorded as CPL11.
[0105] The battery assembly process is the same as in Example 1, and the performance test results are listed in Table 1.
[0106] Comparative Example 4
[0107] (1) dissolving sodium carboxymethyl cellulose in deionized water and stirring at room temperature for 24 hours to prepare a sodium carboxymethyl cellulose aqueous solution with a mass concentration of 1.2%;
[0108] (2) dissolving polyethylene oxide in deionized water and stirring at room temperature for 24 hours to prepare a polyethylene oxide aqueous solution with a mass concentration of 1.2%, and adding lithium salt LiBOB according to a mass ratio of polyethylene oxide to lithium salt of 12:1 to obtain a polyethylene oxide-lithium salt mixed solution;
[0109] (3) mixing the sodium carboxymethyl cellulose aqueous solution and the polyethylene oxide-lithium salt mixed solution in a mass ratio of 1:2, and stirring at room temperature for 12 hours to obtain an electrode material binder;
[0110] (4) The electrode material binder prepared in step (3) is mixed with the lithium-rich manganese positive electrode material 0.5Li2MnO3·0.5LiNi 0.33 Co 0.33 Mn 0.33 O2 and Super P were mixed into a slurry in a mass ratio of 10:85:5; after being stirred evenly, the slurry was coated on an aluminum foil current collector to obtain a positive electrode sheet, which was recorded as CPL12.
[0111] The battery assembly process is the same as in Example 1, and the performance test results are listed in Table 1.
[0112] Comparative Example 5
[0113] (1) dissolving sodium carboxymethyl cellulose in deionized water and stirring at room temperature for 24 hours to prepare a sodium carboxymethyl cellulose aqueous solution with a mass concentration of 1.2%;
[0114] (2) dissolving polyethylene oxide in deionized water and stirring at room temperature for 24 hours to prepare a polyethylene oxide aqueous solution with a mass concentration of 1.2%, and adding lithium salt LiBOB according to a mass ratio of polyethylene oxide to lithium salt of 12:1 to obtain a polyethylene oxide-lithium salt mixed solution;
[0115] (3) mixing the sodium carboxymethyl cellulose aqueous solution and the polyethylene oxide-lithium salt mixed solution in a mass ratio of 1:3, and stirring at room temperature for 12 hours to obtain an electrode material binder;
[0116] (4) The electrode material binder prepared in step (3) is mixed with the lithium-rich manganese positive electrode material 0.5Li2MnO3·0.5LiNi 0.33 Co 0.33 Mn 0.33 O2 and Super P were mixed into a slurry in a mass ratio of 10:85:5; after being stirred evenly, the slurry was coated on an aluminum foil current collector to obtain a positive electrode sheet, which was recorded as CPL13.
[0117] The battery assembly process is the same as in Example 1, and the performance test results are listed in Table 1.
[0118] Table 1
[0119]
[0120] By comparing Examples 1-4 and Comparative Example 1, it can be seen that the electrochemical properties of lithium-rich manganese layered oxides can be better improved by introducing a high ionic conductivity PEO polymer matrix and a high voltage resistant pentafluorophenylboric acid PFBBA; as the content of pentafluorophenylboric acid PFBBA increases, the electrochemical properties are further improved.
[0121] By comparing Examples 1-4 and Comparative Example 2, it can be seen that by introducing a high ionic conductivity PEO polymer matrix and a lithium salt, the ionic conductivity can be better improved and the electrochemical performance can be further enhanced.
[0122] Comparison of Examples 1-4 and Comparative Examples 3-5 shows that the introduction of too much high ionic conductivity PEO polymer matrix destroys the stability of the binder itself, thereby reducing the electrochemical performance of the lithium-rich manganese layered oxide.
[0123] By comparing Examples 5-7, it can be seen that the electrochemical properties of the lithium-rich manganese layered oxide can be better improved by introducing a high ionic conductivity PEO polymer matrix and a high voltage resistant tetramethylborate TMB; as the content of tetramethylborate TMB increases, the electrochemical properties are further improved.
[0124] By comparing Example 1 with Comparative Example 1, it can be seen that the introduction of the high ionic conductivity PEO polymer matrix effectively improves the electrochemical performance of the lithium-rich manganese layered oxide. Fig.13 and Fig.18 The TEM images of the products prepared in Example 4 of the present invention and Comparative Example 1 after 400 cycles show that after the introduction of a binder having high ionic conductivity and high voltage resistance, the lithium-rich manganese surface has a uniform CEI film. In contrast, an uneven CEI film is formed on the lithium-rich manganese surface using sodium carboxymethyl cellulose as a binder.
Claims
1. A method for preparing a binder having high ionic conductivity and high voltage resistance, characterized in that: The steps include: Step 1: Prepare polyethylene oxide-lithium salt mixture Dissolve polyethylene oxide in deionized water and stir at room temperature for 24 hours to prepare a polyethylene oxide solution, and add lithium salt in a polyethylene oxide to lithium salt mass ratio of 12:1 to obtain a polyethylene oxide-lithium salt mixed solution; Step 2: Preparation of electrode material binder The sodium carboxymethyl cellulose aqueous solution and the polyethylene oxide-lithium salt mixed solution were mixed in a mass ratio of 10:1, and stirred at room temperature for 12 hours to obtain an electrode material binder; Step 3: Preparation of high ionic conductivity and high voltage resistant electrode material binder The electrode material binder and the high voltage resistant additive are mixed in a mass ratio of 10:(0-1.5), wherein the high voltage resistant additive is one or two of pentafluorophenylboric acid PFBBA and tetramethyl borate (TMB); and an electrode material binder with high ionic conductivity and high voltage resistance is obtained.
2. The method for preparing a binder having high ionic conductivity and high voltage resistance according to claim 1, characterized in that: The electrode material binder and the high voltage resistant additive are in a mass ratio of 10:(0.5-1.5).
3. The method for preparing a binder having high ionic conductivity and high voltage resistance according to claim 1, characterized in that: The lithium salt is at least one of lithium hexafluorophosphate LiFP6, lithium tetrafluoroborate LiBF4, lithium bis(oxalatoborate) LiBOB, lithium bis(trifluoromethylsulfonyl)imide LiTFSI, lithium bis(fluorooxalatoborate) LiODFB, and lithium bis(fluorosulfonyl)imide LiFSI.
4. The method for preparing a binder having high ionic conductivity and high voltage resistance according to claim 1, characterized in that: The mass concentration of the sodium carboxymethyl cellulose solution is 1.2%.
5. The method for preparing a binder having high ionic conductivity and high voltage resistance according to claim 1, characterized in that: When preparing the polyethylene oxide aqueous solution, the stirring time is 24 hours.
6. Use of the binder having high ionic conductivity and high voltage resistance as claimed in claim 1 in preparing a positive electrode.
7. The use of the binder with high ionic conductivity and high voltage resistance in preparing an electrode positive electrode according to claim 6, characterized in that: The electrode material binder, active material and conductive agent are mixed to prepare pulp. The high-voltage resistant additive is added during the pulping process. The high-voltage resistant additive is one or two of pentafluorophenylboric acid PFBBA and tetramethyl borate (TMB). The amount of the high-voltage resistant additive added accounts for 0.5-1.5% of the total mass of the electrode material binder, active material and conductive agent. After stirring evenly, the mixture is coated on an aluminum foil current collector to obtain a positive electrode sheet.
8. The use of the binder with high ionic conductivity and high voltage resistance in preparing an electrode positive electrode according to claim 7, characterized in that: The mass ratio of the electrode material binder to the active material and the conductive agent is 10:85:
5.
9. The use of the binder with high ionic conductivity and high voltage resistance in preparing an electrode positive electrode according to claim 7, characterized in that: The conductive agent is one or two of Super P and acetylene black; the active material is one of NCM811 / NCM622 / NCM532 ternary material, lithium cobalt oxide, lithium nickel oxide, and lithium-rich manganese material; the conductive agent is one or more of Super P, acetylene black, carbon nanotubes or graphene.
10. The use of the binder with high ionic conductivity and high voltage resistance in preparing an electrode positive electrode according to claim 7, characterized in that: The lithium-rich manganese material is 0.5Li2MnO3·0.5LiNi 0.33 Co 0.33 Mn 0.33 O2.
Citation Information
Patent Citations
Silicon-based composite electrode and preparation method and application thereof
CN113206213A
3D printed solid-state battery and preparation method and application thereof
CN114069024A
Method for improving rate capability of battery and lithium ion battery
CN114122324A
Battery electrolyte and lithium ion battery
CN115051030A
Preparation method of high-specific-energy composite solid positive electrode
CN115312776A